2013
DOI: 10.1257/mac.5.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Effects of Bank Failures from a Natural Experiment in Mississippi during the Great Depression

Abstract: I examine the causal effect of bank failures during the Great Depression using the quasi-experimental setup of Richardson and Troost (2009). The experiment is based on Mississippi being divided into two Federal Reserve districts, which followed different policies for liquidity provision. This translated into variation in bank failures across the state. Employing a plant-level sample from the Census of Manufactures, I find that banking failures had a negative effect on revenue stemming from a fall in physical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…If the economy had maintained the momentum of the recovery and avoided the recession of 1937-1938, GDP would have reached trend in 1938. 4 To large extent, therefore, explaining the slow recovery is the same as explaining the recession of [1937][1938]. This challenge is taken in Eggertsson and Pugsley (2006), which attributes the recession in 1937 to the administration's reneging on its commitment to inflation, an interpretation that is consistent with this article.…”
supporting
confidence: 57%
“…If the economy had maintained the momentum of the recovery and avoided the recession of 1937-1938, GDP would have reached trend in 1938. 4 To large extent, therefore, explaining the slow recovery is the same as explaining the recession of [1937][1938]. This challenge is taken in Eggertsson and Pugsley (2006), which attributes the recession in 1937 to the administration's reneging on its commitment to inflation, an interpretation that is consistent with this article.…”
supporting
confidence: 57%
“…Previous research has shown that there is a strong relationship between local economic activity and the condition of the financial sector (e.g. Rajan and Zingales 1998, Petersen and Rajan 2002, Guiso, Sapienza, and Zingales 2004, Gilje 2017, and more recently in a historical context Carlson, Correia, and Luck 2019, Ziebarth 2013and Lee and Mezzanotti 2014. We provide direct evidence on how the condition of financial markets may also shape the recovery from a shock.…”
Section: Introductionmentioning
confidence: 99%
“…3 In contemporaneous work, Lee and Mezzanotti (2015) find a contraction in the city-industry employment levels of manufacturing establishments in response to local bank failures. Ziebarth (2013) finds that tight monetary policy, which contributed to the intensity of bank failures, led to lower employment at the county level but had no differential effects at the establishment level. These studies use establishment data obtained from the Census of Manufactures, and therefore lack direct information on firms' (or the establishments') financial health.…”
mentioning
confidence: 95%
“…the difficulties banks experienced likely contributed to the severity and persistence of the recession by increasing the real cost of intermediation. Recent work has revisited this question empirically with the aim of providing causal evidence for the effects of bank failures on a variety of outcomes, including income growth (Calomiris and Mason, 2003), industrial output (Mladjan, 2016), business revenues (Ziebarth, 2013), and employment (Ziebarth, 2013;Lee and Mezzanotti, 2015). 5 These studies obtain identification primarily from variation in the health of banks across space, but they lack information on the firms' financial conditions.…”
mentioning
confidence: 99%